Pengukuran Nilai Sumber Daya Manusia pada Lembaga Pendidikan dengan Compensation Model - Harimurti, Yohanes (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2002)
This study gives a description about the value of the human capital associated with a service enterprise. However, the idea about human value accounting still becomes controvercy until now. The objective of this study is to provide a practical measurement procedure about human capital, specifically in using the economics concept of human capital. On the economics concept, the value of human capital embodied in a person of age t is the present value of his/her remaining future earnings from employment.